- #1

sssr

- 4

- 0

Hi

I have to solve this equation using laplace transform

ty''+(t-1)y'+y=t^2 y(0)=0 y'(0)=0

I tried it using MATLAB and get to this point

(Int(-2/s^4*exp(1/2*s*(s+6)),s)+C1)*exp(-1/2*s*(s+6))

I think I've gone wrong somewhere

Any Help would be appreciated.

Thanks

I have to solve this equation using laplace transform

ty''+(t-1)y'+y=t^2 y(0)=0 y'(0)=0

I tried it using MATLAB and get to this point

(Int(-2/s^4*exp(1/2*s*(s+6)),s)+C1)*exp(-1/2*s*(s+6))

I think I've gone wrong somewhere

Any Help would be appreciated.

Thanks

Last edited: